Factors influencing summer farms management in the Alps - Enrico Sturaro; Mara Thiene; Giampaolo Cocca; Meriem Mrad; Tiziano Tempesta; Maurizio Ramanzin (Italian Journal of Animal Science, 2013)
This paper aimed at investigating the recent evolution and the present status of the summer farms in the Veneto region, north-eastern Italian Alps, a study area that is a typical example of the recent abandoning and intensification trends in the livestock farming of European mountains. An on-farm survey was conducted on 484 active units to collect information on structural and technical features of the farms, on herd composition and management practices, and on environmental and management features of their pastures. A clustering approach based on structural and technical features subdivided the summer farms in two clusters. One cluster included 189 units, mostly owned by municipalities and other public institutions, with renovated structures and modern equipment, while the other included 295 summer farms, mostly owned by privates, with often obsolete structures and equipment. Herd composition and management practices were more intensive in the public than in the private cluster, while environmental and management features of pastures differed only marginally. Socio-economic viability, estimated with a multicriteria approach, was higher for “public” than “private” summer farms. Our results indicate that the kind of ownership has been the main determinant of the recent evolution and the present status of summer farms, and that the traditional, strict link between the management of the summer farms and the optimal conservation of their pastures has been disrupted. These findings must be considered in order to devise effective agricultural and environmental policies in mountain areas.